Microstructure and strengthening effect of coated diamond particles on the porous aluminum composites - Parveez, Bisma; Jamal, Nur Ayuni; Aabid, Abdul; Baig, Muneer (MDPI, 2023)
In this work, porous Al alloy-based composites with varying Ti-coated diamond contents (0, 4, 6, 12 and 15 wt.%) were prepared, employing the powder metallurgy route and using a fixed amount (25 wt.%) of polymethylmethacrylate (PMMA) as a space holder. The effects of the varying wt.% of diamond particles on the microstructure, porosities, densities and compressive behaviors were systematically evaluated. The microstructure study revealed that the porous composites exhibited a well-defined and uniform porous structure with good interfacial bonding between the Al alloy matrix and diamond particles. The porosities ranged from 18% to 35%, with an increase in the diamond content. The maximum value of plateau stress of 31.51 MPa and an energy absorption capacity of 7.46 MJ/m3 were acquired for a composite with 12 wt.% of Ti-coated diamond content; beyond this wt.%, the properties declined. Thus, the presence of diamond particles, especially in the cell walls of porous composites, strengthened their cell walls and improved their compressive properties.